Steroids and doping in sports : a reference handbook - Newton, David E. (Contemporary world issues., 2018)
This book introduces one of the most controversial issues in modern society--steroid abuse among athletes--as well as to the ongoing debate over the use and misuse of illegal substances in amateur and professional sporting events. It provides readers with updated critical and objective information about steroids and doping in sports in the United States and worldwide, and discusses the history and background, current problems, controversies, and possible solutions.